Review on advanced technologies for the recovery of aluminum from waste carton packaging using pyrolysis - Mantegazini, Diunay Zuliani; Neves, Fernando Luiz; Xavier, Thiago Padovani; Bacelos, Marcelo Silveira (Brazilian Journal of Production Engineering, 2021)
Pyrolysis is a green technology that makes it possible to separate aluminum from polyethylene in Tetra Pak packaging. This alternative can be used to reduce the environmental impact resulting from the inadequate destination of these modern wastes. In addition, recycling makes it possible to recover materials with high added value. For the recovery of aluminum and paraffinic oils from waste carton packs, this review article aims to highlight advances in science and technology for the recovery of aluminum from carton packs. Among the reactors analyzed, spouted beds and fluidized beds can be pointed out as new opportunities and great successes in the sector in the coming years. Regarding the economic potential, two factors point to the pyrolysis of waste from carton packaging as a promising technique: the added value of recycled materials and the energy savings of the process. Based on the economic analysis, pyrolysis has a positive economic potential of 190.5 US$/per ton of product. When compared to the traditional aluminum production process, pyrolysis can save 0.745 MWh for every ton of recovered carton pack. With regard to the profitability of the process, plasma pyrolysis has an accumulated cash ratio of 3.27 million and a rate of return on investment of 2.04%, proving to be an attractive investment.
Keywords: Pyrolysis; Carton Packages; Aluminum Recovery; Spouted Beds